The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/poms.12035
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Bank and Trade Credits: Theoretical Analysis and Empirical Evidence

Abstract: This study investigates the roles of bank and trade credits in a supply chain with a capital‐constrained retailer facing demand uncertainty. We evaluate the retailer's optimal order quantity and the creditors' optimal credit limits and interest rates in two scenarios. In the single‐credit scenario, we find the retailer prefers trade credit, if the trade credit market is more competitive than the bank credit market; otherwise, the retailer's preference of a specific credit type depends on the risk levels that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
117
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(124 citation statements)
references
References 50 publications
6
117
0
1
Order By: Relevance
“…They conclude that a trade credit is preferable to a bank credit, seen from the supplier's point of view. Cai et al perform a similar research to Kouvelis and Zhao and draw the similar conclusions. Supplementing these studies, Jing and Seidmann studied a 2‐echelon supply chain composed of a manufacturer and a capital‐constrained retailer.…”
Section: Literature Reviewsupporting
confidence: 59%
“…They conclude that a trade credit is preferable to a bank credit, seen from the supplier's point of view. Cai et al perform a similar research to Kouvelis and Zhao and draw the similar conclusions. Supplementing these studies, Jing and Seidmann studied a 2‐echelon supply chain composed of a manufacturer and a capital‐constrained retailer.…”
Section: Literature Reviewsupporting
confidence: 59%
“…In addition, some literatures considered other respects in the bank financing model, for instance, [6] incorporated the firm's moral risk into the financing model, and analyzed the comparison between trade and bank credit for the supply chain. Cai et al [23] showed that bank credit is less effective than trade credit in mitigating double marginalization with relatively low production cost.…”
Section: Supply Chain Financementioning
confidence: 99%
“…Jing et al [10] and Jing and Seidmann [11] further compare the efficiency between BCF and TCF for a capital-constrained retailer, and it is found that when production cost is relatively low, TCF will be more effective than BCF in mitigating double marginalization. Cai et al [19] prove that BCF and TCF are either complementary or substitutable for a capitalconstrained retailer through both theoretical and empirical studies.…”
Section: Interface Of Operations and Financing Decisionsmentioning
confidence: 99%